Título Padrão: Ambientes marinhos rochosos nas praias do estado do Ceará, costa equatorial do Brasil - Carneiro, Pedro Bastos de Macêdo; Antônio Rodrigues Ximenes Neto; Caroline Vieira Feitosa; Cristiane Xerez Barroso; Helena Matthews-Cascon; Marcelo de Oliveira Soares; Tito Monteiro da Cruz Lotufo (Arquivos de Ciências do Mar, 2021)
This paper is a literature review on marine hardbottom environments (MHE) that emerge in coastal regions in the Brazilian state of Ceará. This stretch of the Brazilian coast houses several rock formations, which are widely distributed in the intertidal zone. These formations have various origins and composition, ranging from crystalline rocks to biogenic structures, but most are composed by sandstones. These substrates support biodiverse ecosystems that produce valuable environmental goods and services, which have historical and socioeconomic relevance for the state. Despite their importance, they are currently threatened by various types of local and global stressors, and a consistent government effort to protect them is still lacking. There are many knowledge gaps regarding these formations and new studies are needed to support conservation actions involving these ecosystems. Keywords: reef, beachrock, sandstone, intertidal zone, benthos